Does Catheter-Directed Thrombolysis Prevent Postthrombotic Syndrome? - Young-Ah Kim; Shin-Seok Yang; Woo-Sung Yun (Vascular Specialist International, 2018)
Purpose: The aim of this study is to identify risk factors of postthrombotic syndrome (PTS) and evaluate the efficacy of catheter-directed thrombolysis (CDT) for preventing the development of PTS in patients with lower extremity deep vein thrombosis (DVT).